Co-Designing a School-Based Citizen Science Protocol to Investigate Tire-Related Pollutants in Barcelona - Celia Santos-Tapia; Glòria Carrasco-Turigas; Sofia Williamson; Matias Verderau; Francesca De Angelis; Antonia Merola; Nicola Montemurro; Mercè Garí; Mònica Ubalde-López (Journal of Urban Health, 2026)
Abstract Adolescents are both key beneficiaries and underrepresented partners in urban exposure research. We co-designed the CIRCULATE study with students from two secondary schools in the Metropolitan Area of Barcelona to collaboratively develop research questions and a feasible school-based protocol for investigating non-exhaust traffic emissions, specifically tire-related pollutants. Applying an Urban Health Laboratory methodology, the process unfolded in three stages: (i) participatory diagnosis to identify students’ environmental concerns and build a shared understanding of tire-related pollution, (ii) citizen science co-definition and prioritization of research questions within the predefined thematic framework of tire-related chemicals (TRCs), and (iii) collaborative design of a school-compatible study protocol (variables, tools, where and when to sample). Across the two schools, traffic-related pollution consistently emerged as the dominant concern; tires were widely recognized as a pollution source, yet knowledge about tire-wear particles and associated additives was limited. Students produced idea summaries that were iteratively refined into draft research questions and categorized for analysis, prioritizing exposure pathways close to where they live and study. The co-design process proved feasible and context-appropriate for schools, integrating low-cost personal monitoring (passive/low-burden/voluntary silicone wristbands, portable sensors) and biological monitoring (urine samples) with school-level observation and structured discussions to guide near-term interventions. The co-creation process increased literacy, ownership, and motivation to act, and yielded a protocol that may be adapted and tested in future deployments across neighborhoods with varying traffic loads and urban morphologies. Overall, including adolescent perspectives strengthens the relevance and practicality of urban exposure research, surfaces blind spots on tire wear, and mobilizes school-level actions while laying groundwork for larger, comparative deployments.